2006
DOI: 10.1007/s00122-006-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of simple sequence repeat markers for utilizing wide-compatibility genes in inter-subspecific hybrids in rice (Oryza sativa L.)

Abstract: Although pronounced heterosis in inter-subspecific hybrids was known in rice for a long time, its utilization for hybrid rice breeding has been limited due to their hybrid sterility (HS). For the last two decades, however, a few inter-subspecific hybrids have been developed by incorporating wide-compatibility genes (WCG) that resolve HS, into parental lines of these inter-subspecific hybrids. For effective use of WCG, it is necessary to find convenient markers linked to WCG of practical importance. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The reason for the failure to detect polymorphism with the CAPS marker RG140FL/RL in the parental lines of the BC 1 F 1 population could be due to lack of polymorphism between the parental lines in the genomic region amplified by the marker due to narrow genetic diversity. Another reason could be that the CMS line IR62829A is reported to possess hybrid sterility genes (Singh et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the failure to detect polymorphism with the CAPS marker RG140FL/RL in the parental lines of the BC 1 F 1 population could be due to lack of polymorphism between the parental lines in the genomic region amplified by the marker due to narrow genetic diversity. Another reason could be that the CMS line IR62829A is reported to possess hybrid sterility genes (Singh et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Among these deleted fragments, the RM50 SSR locus is linked to S5, a gene that controls sterility in japonica x indica sexual hybrids (Singh et al, 2006), and that is located within a recombination hotspot. Given that the extent of chromatin elimination is higher in the more exotic somatic hybrids, such pressure could affect a number of genomic regions containing genes responsible for wide hybrid sterility, which merits further investigation.…”
Section: Extent Of Dna Loss Following Somatic Hybridization Is Relatementioning
confidence: 99%
“…Therefore, the developmental phase of the S 6 locus-mediated abortion and consequent segregation pattern are both unequivocally distinguished from those mediated by the Cif/cim genes, although the possibility cannot be ruled out that abortions at different developmental phases are caused by pleiotropic effects of a single gene, which would resemble a phenomenon caused by the Tcb1 locus in maize (Kermicle 2006). The hybrid sterility loci, S 1 (Sano 1990), S 5 (Yanagihara et al 1995), S 8 (Singh et al 2006), S 10 (Sano et al 1994, and S 26 (Kubo and Yoshimura 2001), have also been mapped to chromosome 6, a mapping procedure carried out using different pairs of crossing parents. These genes were mapped in chromosomal regions apart from the S 6 locus, and segregation analyses of marker genes tightly linked with these loci also indicated that the segregation distortion caused by these loci was independent of that by the S 6 locus (our unpublished data).…”
Section: Tablementioning
confidence: 99%